Influence of travel and tour website on tourist behaviour to determine destination in Malaysia among IIUM students in Pagoh, Johor. - Borahan, Nur Saiful Amree; Saad, Mazni (2020)
This study is to examine the factors that influence IIUM Pagoh students to use the travel and tour website in Malaysia. This research explores the effectiveness of travel website on students’ travel planning trough information quality, service quality and design quality. This research proposes two research questions which are students in IIUM PAGOH satisfied with current tourism website quality and which one of these website qualities influenced the customer satisfaction that gives impact on the behaviour of selecting tourist destination. This research uses quantitative approach in which questionnaire is used for the instrument and the targeted population is students in IIUM PAGOH. The result is run through descriptive analysis for clustering the demographic, followed by inferential analysis in which this research shows that students’ satisfaction design quality, service quality and information quality have a positive relationship with each other, but not all variables are significant. The data were analyzed using SPSS. This research shows that the functions of Tour and Travel website as well as degree of student satisfaction are present which reflects on the effectiveness of it.